ATUS-Commuting: Stata Code to Calculate Commuting Time in the American Time Use Survey. Issue 1 (25th September 2017) - Kimbrough, Gray
The American Time Use Survey (ATUS) provides extensive information on how Americans spend their time, and has been of particular interest to economists, sociologists, and other researchers. Researchers have sought to study commuting behavior using the ATUS, but its stock time use measures do not measure commuting satisfactorily. This package provides Stata code to implement the previously described trip tour methodology, constructing an appropriate measure of commuting from ATUS activity-level files.